Graphene and MWCNT Printed Films: Preparation and RF Electrical Properties Study. (18th April 2019) - Quaranta, Simone; Giorcelli, Mauro; Savi, Patrizia
Abstract : Carbon materials are well known for being a versatile class of materials able to transmit an electrical signal when used as fillers in composites. Among numerous carbon fillers, carbon nanotubes and graphene have been extensively investigated for the last thirty years. This paper compares graphene and carbon nanotube electrical (i.e., resistive and reactive) properties in the microwave range up to 3 GHz. The transmission and reflection parameters of both the microstrip transmission lines and patch antennas loaded with 33 wt.% of graphene and multiwalled carbon nanotubes (MWCNTs) were analyzed. Interestingly, for an identical composite matrix composition, different scattering parameters stemmed from the different morphology of the films, the diverse interactions between the graphene nanoplatelets, MWCNTs, and polymeric binders in conjunction with the intrinsic electrical characteristics of the two carbon materials.